(untitled) (Revista Rupturas, 2024)
This study investigates the relationship and contribution of research conducted within the Graduate Program in Sustainable Development at the University of Costa Rica to sustainable development. It analyzes 46 theses developed between 2007 and 2023. Through a comprehensive documentary analysis, the study delved into aspects including authorship, gender, nationality, emphases, and the locations and objects of study for each research. This analysis facilitated the identification of three main categories: 1) local communities, 2) organizations, and 3) protected areas. Lastly, the research focus underwent analysis in areas encompassing poverty, hunger, health, education, decent work, responsible production and consumption, alliances, and preservation of terrestrial ecosystems. This analysis facilitated the establishment of direct connections with the Sustainable Development Goals.